Real-world effectiveness of vedolizumab in refractory pouchitis: a focus on biomarker changes during intravenous to subcutaneous transition (POUCHIVED study) - Gimeno-Pitarch, Leticia; Céspedes-Martínez, Elena; Ferreiro-Iglesias, Rocío; Martín-Arranz, María Dolores; Sicilia, Beatriz; Lorca, Inma; Huguet, José; Mesonero, Francisco; Vicente-Lidón, Raquel; Mínguez, Alejandro; Galvez-Martín, Pablo; Serra-Ruiz, Xavier; et al. (Frontiers in Immunology, 2025)
BackgroundChronic antibiotic-refractory pouchitis (CARP) is a complex and often debilitating complication following ileal pouch-anal anastomosis (IPAA). Vedolizumab (VDZ), a gut-selective anti-integrin agent, has shown potential efficacy in this context, but real-world evidence remains limited. This study aimed to evaluate the effectiveness, safety, and treatment persistence of VDZ in patients with CARP, including outcomes after transitioning from intravenous (IV) to subcutaneous (SC) administration.MethodsThis multicenter Spanish study (POUCHIVED) included patients with CARP treated with VDZ. Disease activity was assessed using the modified Pouchitis Disease Activity Index (mPDAI). mPDAI, fecal calprotectin (FC), C-reactive protein (CRP), and serum VDZ levels were recorded at weeks 12, 24, and 52 during IV treatment, and subsequently after switching to SC administration when applicable.ResultsForty-seven patients (66% male; median age 51 years) were included, of whom 53% transitioned to SC VDZ. Most patients presented mild pouchitis at baseline, reflecting early initiation of vedolizumab in clinical practice. IV VDZ therapy led to significant reductions in mPDAI and FC at all evaluated time points: mPDAI decreased from a baseline median of 5 [IQR 3–7] to 3 [2–5], 2 [2–5], and 2 [2–5.8] at weeks 12, 24, and 52, respectively (p<0.05) and FC declined from 443 µg/g [IQR 213–746] at baseline to 329 µg/g [145–701], 193 µg/g [91–412], and 178 µg/g [101–640] at the same intervals. Following the switch to SC VDZ, both mPDAI and FC showed further improvement at week 52, while CRP levels remained unchanged. SC VDZ was associated with higher serum drug concentrations compared to IV. Better clinical outcomes were observed in patients with fewer prior therapies post-surgery, while baseline corticosteroid or immunosuppressant use and prior VDZ exposure before IPAA did not influence response. Treatment persistence was high, and adverse event rates were comparable between IV and SC formulations (8.5% vs. 12%).ConclusionsVDZ is effective and safe for the management of CARP, particularly when used at first line in the treatment course. Transitioning from IV to SC administration maintains clinical remission and is well tolerated in real-world clinical settings.